Application of Project Based Learning Models based on Lesson Study to Improve the Ability to Solve Students' Physics Problems - Arini Rizqa; Khaerus Syahidi (Lembaga Bale Literasi, 2024)
This research is classroom action research that aims to examine the implementation of the Project Based Learning Model with a lesson study to improve the physics problem solving abilities. This research was conducted in class X MIPA 4 SMAN 3 Selong in the even semester of the 2022/2023 school year with 26 learners. This research was conducted in two cycles. The result showed that the application of Project Based Learning Model with a lesson study was able to solve physics problem solving abilities of the student.